Strategi Peningkatan Ekonomi Keluarga Pekerja Di Warung Makan Songkolo Begadang Antang Makassar - Alfiyani Bahar, Siti; Mustafa, Mustari; Kasman, Suf (Universitas Islam Negeri Alauddin Makassar, 2025)
This study presents two main problem formulations, namely: first, what are the strategies for improving the family economy implemented by the workers of the Songkolo Begadang Antang Makassar Food Stall? Second, what are the supporting and inhibiting factors in efforts to improve the economy of the workers' families in the stall? This type of research is qualitative using a descriptive method. This study involved collecting data through in-depth interviews with four workers and the manager of the Songkolo Begadang food stall. This approach aims to understand the experiences and strategies implemented by workers in improving their family economy, as well as the factors that influence the success of these efforts. The results of the study indicate that the strategies for improving the economy of workers' families include managing the main income from work in the stall, diversifying income through side businesses, and utilizing job opportunities in the informal sector. The workers felt significant economic changes, such as the ability to meet the basic needs of the family and reduce dependence on others. However, they also face challenges such as fluctuations in raw material prices, limited time with family, and fluctuations in customer demand.